Immune response to SARS-CoV-2 variants: A focus on severity, susceptibility, and preexisting immunity. Issue 2 (February 2022) - Alefishat, Eman; Jelinek, Herbert F.; Mousa, Mira; Tay, Guan K.; Alsafar, Habiba S.
Abstract: The heterogeneous phenotypes among patients with coronavirus disease 2019 (COVID-19) has drawn worldwide attention, especially those with severe symptoms without comorbid conditions. Immune responses to severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), the causative virus of COVID-19, occur mainly by the innate immune response via the interferon (IFN)-mediated pathways, and the adaptive immunity via the T lymphocyte and the antibody mediated pathways. The ability of the original Wuhan SARS-CoV-2 strain, and possibly more so with new emerging variants, to antagonize IFN-mediated antiviral responses can be behind the higher early viral load, higher transmissibility, and milder symptoms compared to SARS-CoV and are part of the continued clinical evolution of COVID-19. Since it first emerged, several variants of SARS-CoV-2 have been circulating worldwide. Variants that have the potential to elude natural or vaccine-mediated immunity are variants of concern. This review focuses on the main host factors that may explain the immune responses to SARS-CoV-2 and its variants in the context of susceptibility, severity, and preexisting immunity.